2017
DOI: 10.1186/s12934-017-0660-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a C4-dicarboxylate transporter is the key for rerouting citric acid to C4-dicarboxylic acid production in Aspergillus carbonarius

Abstract: BackgroundC4-dicarboxylic acids, including malic acid, fumaric acid and succinic acid, are valuable organic acids that can be produced and secreted by a number of microorganisms. Previous studies on organic acid production by Aspergillus carbonarius, which is capable of producing high amounts of citric acid from varieties carbon sources, have revealed its potential as a fungal cell factory. Earlier attempts to reroute citric acid production into C4-dicarboxylic acids have been with limited success.ResultsIn th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Recently, the genes (gcd, gad, pqq) encoding the related enzymes have been investigated (de Werra et al, 2009;Hsu et al, 2015;An and Moe, 2016). In addition to OA biosynthesis, some genes encoding OA transporters have been identified and characterized in bacteria, such as ttdT, dct, JEN, oxlT (Kim and Unden, 2007;Iyalomhe et al, 2014;Becker, 2015;de Lima et al, 2016;Yang L et al, 2017), although their involvement in solubilizing sparingly soluble Pi is largely unknown. For the mobilization of Po, P mineralizing bacteria exude nonspecific phosphatase (phosphomonoesterase, phosphodiesterase, phosphotriesterase), phytase, phosphonatase or C-P lyase to hydrolyze Po and release orthophosphate (Eivazi and Tabatabai, 1977;Nannipieri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the genes (gcd, gad, pqq) encoding the related enzymes have been investigated (de Werra et al, 2009;Hsu et al, 2015;An and Moe, 2016). In addition to OA biosynthesis, some genes encoding OA transporters have been identified and characterized in bacteria, such as ttdT, dct, JEN, oxlT (Kim and Unden, 2007;Iyalomhe et al, 2014;Becker, 2015;de Lima et al, 2016;Yang L et al, 2017), although their involvement in solubilizing sparingly soluble Pi is largely unknown. For the mobilization of Po, P mineralizing bacteria exude nonspecific phosphatase (phosphomonoesterase, phosphodiesterase, phosphotriesterase), phytase, phosphonatase or C-P lyase to hydrolyze Po and release orthophosphate (Eivazi and Tabatabai, 1977;Nannipieri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the mae1 gene was critical in both strain backgrounds and led to an almost three times higher succinate titer in the wildtype (REF‐6) and a twofold increase in the TAM strain (TAM‐6) compared with the strains carrying the succinate synthesis pathway but lacking the transporter. In several other studies, introduction of a heterologous transporter function has been shown to be critical for the extracellular accumulation of several organic acids including succinate …”
Section: Resultsmentioning
confidence: 99%
“…The expression of the mae1 gene was critical in both strain backgrounds and led to an almost three times higher succinate titer in the wildtype (REF-6) and a twofold increase in the TAM strain (TAM-6) compared with the strains carrying the succinate synthesis pathway but lacking the transporter. In several other studies, introduction of a heterologous transporter function has been shown to be critical for the extracellular accumulation of several organic acids including succinate [5,18,36] The TAM strain did not produce ethanol, the main byproduct formed by the wild-type strain in concentrations as F I G U R E 2 Comparison of the reference and TAM strains engineered for succinate production. The strains were cultivated in mineral salt medium with 5% glucose as substrate and supplemented with 22 mM formate under microaerobic conditions (shaking frequency 90 rpm).…”
Section: Chromosomal Expression Of the Heterologous Pathways In The Wmentioning
confidence: 96%
“…Expression of NADH-dependent fumarate reductase from Trypanosoma brucei increased succinic production from 3.8 to 16.2 g/L while negatively affecting malic and citric acid production [37]. When the same fumarate reductase gene was expressed in an engineered strain of Aspergillus carbonarius lacking the glucose oxidase gene the acid production profile was unchanged, yet increased succinic production up to 16 g/L when a C4-dicarboxylate transporter was overexpressed [38]. The studies highlight the need to consider organic acid transport in organisms that do not naturally secrete the target acid.…”
Section: Table 5 Example Solution From Evolution Of Succinic Acid Promentioning
confidence: 99%